Assessing health professionals' perception of health literacy in Rhode Island community health centers: a qualitative study - Mary L. Greaney; Sherrie F. Wallington; Sankeerth Rampa; Vivian S. Vigliotti; Carol A. Cummings (BMC, 2020)
Abstract Background Limited health literacy is linked with poor health behaviors, limited health care access, and poor health outcomes. Improving individual and population health outcomes requires understanding and addressing barriers to promoting health literacy. Methods Using the socio-ecological model as a guiding framework, this qualitative study (Phase 1 of a larger ongoing project) explored the interpersonal and organizational levels that may impact the health literacy levels of patients seeking care at federally qualified community health centers (FQCHCs) in Rhode Island. Focus groups were conducted with FQCHC employees (n = 37) to explore their perceptions of the health literacy skills of their patients, health literacy barriers patients encounter, and possible strategies to increase health literacy. The focus groups were audio-recorded and transcribed, and transcripts were coded using a process of open, axial, and selective coding. Codes were grouped into categories, and the constant comparative approach was used to identify themes. Results Eight unique themes centered on health literacy, sources of health information, organizational culture's impact, challenges from limited health literacy, and suggestions to ameliorate the impact of limited health literacy. All focus group participants were versed in health literacy and viewed health literacy as impacting patients' health status. Participants perceived that some patients at their FQCHC have limited health literacy. Participants spoke of themselves and of their FQCHC addressing health literacy through organizational- and provider-level strategies. They also identified additional strategies (e.g., training staff and providers on health literacy, providing patients with information that includes graphics) that could be adopted or expanded upon to address and promote health literacy. Conclusions Study findings suggest that strategies may need to be implemented at the organizational-, provider-, and patient- level to advance health literacy. The intervention phase of this project will explore intervention strategies informed by study results, and could include offering health literacy training to providers and staff to increase their understanding of health literacy to include motivation to make and act on healthy decisions and strategies to address health literacy, including the use of visual aids.